THE IMPORTANCE ROLE OF COMPETENCY-BASED ON TRAINING, MOTIVATION AND ORGANIZATIONAL CULTURE IN IMPROVING THE EMPLOYEE PERFORMANCE IN EDUCATION AND RESEARCH TRAINING CENTERS AND HR DEVELOPMENT AT THE MINISTRY OF COMMUNICATION AND INFORMATICS - Eka Budi Febriyarso; Sangkala Ruslan (Dinasti Publisher, 2021)
This research has intended to reveal the impact caused by training, motivation and organizational culture on employee performance at the BLSDM Education and Training Center of the Ministry of Communication and Informatics. This research type was included in descriptive quantitative through distributing questions to employees on a Likert scale. The respondents used as many as 40 employees with help from SPPS25 software program, data analysis was carried out by validity, reliability, and some linear regression correlation. The sampling technique obtained from its sample of respondents with the data analysis technique used was multiple linear regression. The results showed that; (1) Training had a significant effect on employee performance; (2) Motivation has a significant impact on employee performance; (3) Organizational culture had a significant impact on employees.